Synthesis And Application Of Glycerin Pitch-Derived Activated Carbon For Model Fuel Oil Desulfurization And Electrode Use - Zulkefli, Maryam Solehah (2024)
Desulfurization of fuel is crucial in meeting environmental regulations in reducing the sulfur content to minimize air pollution and protect human health. Adsorptive desulfurization (ads) has emerged as a viable and efficient method for sulfur compounds removal from diesel fuel. This method requires the ability of adsorbents, such as activated carbon (acs) to selectively capture sulfur-containing compounds. Activated carbons was produced from glycerin pitch, a natural resource and industrial waste material, through the wet impregnation method employing activating agents, namely phosphoric acid (h3po4), and ferum nitrate (fe(no3)3.9 h2o). The primary aim of this study is to emphasize the potential of glycerin pitch activated carbon as an efficient and eco-friendly material means to attain ultra-low sulfur fuel standards. The prepared activated carbons were characterized by x-ray diffraction (xrd), nitrogen absorption analysis (na), field emission scanning electron microscopy-energy dispersion x-ray (fesem and edx), fourier transform infrared spectroscopy (ftir), thermogravimetric analysis (tga). Acs impregnated with phosphoric acid have exceptionally high surface area (860 m2/g) and porous structure (0.4012 cm3/g) which provides ample sites for adsorption of sulfur compounds such as dibenzothiophene (dbt).